March Madness in the Collegiate Sport Workplace: Cultural Implications for Sport Employees - Oja, Brent D.; Hazzaa, Rammi N.; Wilkerson, Zachary; Bass, Jordan R. (Journal of Intercollegiate Sport, 2018)
Drawing upon Schein and Schein’s three-level conceptual framework of organizational culture, the purpose of this study was to examine how organizational culture and a sense of community manifest within intercollegiate athletics departments during March Madness. Considering the popularity of intercollegiate sport and March Madness, it is important for scholars to understand how organizational culture may influence the attitudes and behaviors of collegiate sport employees in the workplace. Thus, semi-structured interviews and observations were conducted to better understand how culture, community, and the phenomenon of March Madness traverse. Analysis of the data revealed a unique organizational culture within intercollegiate athletics departments, distinguishing them from other nonsport organizations. It was also discovered that socialization processes occur during March Madness, which can foster a sense of community. Implications for these findings are discussed and practical recommendations for collegiate athletics departments are provided.